2007
DOI: 10.1080/00268970701361322
|View full text |Cite
|
Sign up to set email alerts
|

Non-Maxwell slippage induced by surface roughness for microscale gas flow: a molecular dynamics simulation

Abstract: Rarefied gas flows in rough microchannels are investigated by non-equilibrium molecular dynamics simulations. The surface roughness is modelled by an array of triangular modules. The Maxwell slip model is found to break down due to the surface roughness for gas flows in microchannels with large surface roughness. Non-Maxwell slippage shows that the slip length is smaller than that predicted by the Maxwell model and is nonlinearly related to the mean free path. For larger surface roughness and smaller Knudsen n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…As an effective and important numerical method, a MD method has been employed for microfluidic systems successfully in much research [20,[22][23][24][26][27][28][29][30][31][32]. Based on Newton's second law, the motion equations of gas molecules are integrated using a leapfrog-Verlet algorithm [26] with a time step dt.…”
Section: Methodsmentioning
confidence: 99%
“…As an effective and important numerical method, a MD method has been employed for microfluidic systems successfully in much research [20,[22][23][24][26][27][28][29][30][31][32]. Based on Newton's second law, the motion equations of gas molecules are integrated using a leapfrog-Verlet algorithm [26] with a time step dt.…”
Section: Methodsmentioning
confidence: 99%
“…Similar behavior is observed in many previous works performed with different simulation methods. For example, Cao [45] studied the surface roughness effect in microscale gas flow by a molecular dynamics simulation and present negative slip for surface roughness equal to 6 nm. Moreover, negative velocities are observed in Guo et al [46] who studied the slip behavior of dense fluid flows in the nanometer scale using a kinetic model and Molecular Dynamics simulations.…”
Section: Flow Velocitymentioning
confidence: 99%
“…[48][49][50][51][52] A number of parameters that affect the fluid behavior, and consequently the performance of nanofluidics, can be determined using MD, for example, the wall-fluid interactions and the wetting properties of the surface. 53,54 Classical molecular modeling is also widely applied in bioflows. [55][56][57][58][59] In a recent study, 56 for example, molecular simulations were employed to exploit the effects of shock waves on biological tissues, and the numerical studies revealed that the shock wave leads to an increased diffusion coefficient and therefore makes the membrane transiently more permeable, which can assist drug delivery.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…To investigate the effect of the aforementioned parameters on the TMAC and gain a better understanding of the physical processes involved, MD simulations have been employed in a number of studies. 51,109,[115][116][117][118][119] In this example, MD simulations are utilized in order to specify the TMAC for a specific solid-gas combination at constant temperature. The problem considered is a Couette flow of Argon between two solid platinum surfaces.…”
Section: Example: Accommodation Coefficient Calculationmentioning
confidence: 99%